Method and organization for expert evaluating of rehabilitation services for lower limb prosthetics: problems and solutions - Yu. B. Golubeva; V. G. Suslyaev; K. K. Shcherbina; L. M. Smirnova; V. V. Galaudina; G. V. Chekushina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Prosthetics of the lower limb after amputation restores the patient's ability to move and self-care. Preparation and prosthetics in the early stages after amputation, in the absence of contraindications, improves the physical, psycho-emotional state of patients, reduces the risk of complications due to forced exercise and exacerbation of concomitant somatic pathology, as well as increases exercise tolerance, restores mobility, functioning after amputation.The aim of the work is to improve the quality of life of patients with mobility disabilities.Materials and methods. The information base of the study was the normative legal acts of the Russian Federation, standards, clinical recommendations defining the existing system of providing rehabilitation services for prosthetics of the lower limb.Conclusion. Unsatisfactory prosthetics of the limb after amputation negatively affects the quality of life of the patient. For this reason, the assessment of the rehabilitation service of prosthetics of the lower limb, including using the tools of the International Classification of Functioning, Disability and Health, is both relevant and necessary.